Validation of the Chinese version of the diabetes health profile to predict the impact of mobile health education on quality of life in type 2 diabetes patients - Lyu, Xiaokang; Zeng, Jinmei; Lin, Jingna; Song, Yixuan; Yang, Tingting; Hou, Wenjing (Frontiers in Public Health, 2024)
Purpose The Diabetes Health Profile (DHP18), initially created in the United Kingdom, currently lacks a Chinese version. This study endeavors to authenticate the Chinese adaptation of the DHP18 and assess the influence of mobile health (mHealth) education intervention on the quality of life of individuals living with diabetes. Patients and methods The study included 470 Type 2 diabetes Mellitus (T2DM) patients (204 men, 266 women), spanning an age range of 19–79 years, with an average age of 54 ± 12.40 years. Data analysis employed Jamovie and Mplus software. Moreover, test–retest reliability was evaluated in 52 hospitalized T2DM patients through two repeated measurements taken 4 weeks apart. Results The Chinese version DHP18 scale exhibited high reliability, evidenced by a Cronbach’s alpha of 0.88, and coefficient of test–retest reliability of 0.84. Individual subscales also demonstrated strong reliability, ranging from 0.76 to 0.84, with test–retest reliability spanning from 0.71 to 0.74. Confirmatory Factor Analysis (CFA) employing a three-factor structure (χ2 = 294.69, GFI = 0.92, TLI = 0.91, RMSEA = 0.05, SRMR = 0.06) validated the scale’s construct validity. Notably, there was a statistically significant difference (p < 0.05) in the quality of life between Type 2 diabetes patients using mHealth education intervention and those without mHealth education intervention. Mediation analysis revealed that Appraisal of Diabetes (ADS) and Self-Management Efficacy (SED) mediated the effects of Psychological Distress (PD) and Behavior Adherence (BA) on quality of life, both significant direct and indirect effects (p < 0.001). In addition, Dietary Abstinence (DE) displayed significant overall impact (β = −0.13, p < 0.001) and indirect influence (β = −0.10, p < 0.01) on diabetic patients’ quality of life, though lacking a significant direct effect (β = −0.03, p = 0.38). Conclusion The Chinese version of the Diabetes Health Profile Scale meets stringent psychometric standards and stands as an appropriate measurement tool for Chinese T2DM patients, maintaining comparable results to the original scale’s structure. The mHealth education intervention yielded a notably positive impact on the quality of life among T2DM patients. Mediation analysis revealed that the three dimensions of the DHP were mediated by Appraisal of Diabetes and Diabetes Self-Management Efficacy, partially mediated by Psychological Distress and Behavior Adherence, and fully mediated by Dietary Abstinence, providing insight into the positive effects of the mHealth model on the quality of life of diabetic patients.